DARI IRIGASI KE INTEGRASI SOSIAL : TELAAH SUBAK WINGIN DALAM MEMUPUK TOLERANSI DI BANJAR DINAS BUKIT SARI DESA TEGALINGGAH. - Ridho, Rasyid; Sukadi, Sukadi (Ganesha Civic Education Journal, 2025)
This study examines the role of Subak Wingin in Banjar Dinas Bukit Sari, Tegalinggah Village, Buleleng, Bali, in fostering tolerance in a multi-ethnic, multi-cultural, and multi-religious society. Subak, a traditional irrigation system, is a socio-religious entity that integrates water management with Balinese social, cultural, and spiritual values, based on the Tri Hita Karana philosophy. This location selection is relevant because Bali, although considered homogeneous, has long been inhabited by diverse ethnicities and religions. This qualitative research with a case study describes the role of Subak Wingin in fostering tolerance and social integration. As a result, the value of tolerance is concretely applied in the fair distribution of water based on need and deliberation. As a result, the value of tolerance is concretely applied in the fair distribution of water based on need and deliberation. Tolerance is also evident in deliberations involving members of various religions (Hindu and Muslim).